SKREENING POTENSI ANTIBAKTERI EKSTRAK Padina australis Hauck TERHADAP BAKTERI Vibrio harveyii - Mohamad Gazali; Eri Safutra (JURNAL PERIKANAN TROPIS, 2016)
Nowadays, a lot of research about the treatment a safe and environmentally sound which uses natural ingredients, one of which seaweed. In the last decade, a wide variety of structures is very unique bioactive compounds from algae isolates have been isolated. But, the resource utilization of bioactive compound from algae has not been done. This study aimed to test the ability of marine macroalgae P. australis Hauck in producing antibacterial compounds Vibrio harveryi. The existence of macroalgae P. australis antibacterial producer is expected to decrease the number of pathogenic bacteria, so as to decrease the likelihood of developing a disease that attacks fish. The research was conducted in two laboratories, the Laboratory of Biological MIPA Universitas Syiah Kuala, Banda Aceh and Brackish Water Aquaculture Institute (BBAP) Batee Ujong, Aceh Besar. Marine macroalgae taken from the waters around Labuhan Haji South Aceh District. The location was selected because of macroalgae in the area are plentiful because the waters are clean. Based on phytochemical test on  P. australis extract containing flavonoids, tannins and saponins. The results of measurements of inhibition zone formed in each treatment obtained the largest inhibition zone at 12:55 mm on a 80% concentration of the extract. While the smallest inhibitory zone at 6:19 mm at a concentration of 100%. Thus, inhibition zone on extracts of P. australis against V. harveyi bacteria at a concentration of 80% is the optimum inhibition of the extract.